2013
DOI: 10.1016/s0254-6272(14)60012-1
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial effects of conception and governor vessel electroacupuncture and human umbilical cord blood-derived mesenchymal stem cells on pathomorphologic lesion and cellular apoptosis in rats with cerebral ischemia/reperfusion

Abstract: HUCB-MSCs improve pathological lesions and inhibit the cellular apoptosis around the cerebral ischemic area. EA at conception and governor vessels also improve pathological lesion and inhibit the cellular apoptosis in rats treated with HUCB-MSCs transplantation, which effects were superior to that of simple HUCB-MSCs transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…It has been shown that, transplantation of human umbilical cord blood mesenchymal stem cells (hUCB-MSCs) decreases the number of activated microglia and inhibits the permeation of immune cells and cellular apoptosis in the brain after ischemic brain injury (Yang et al., 2013; Zhu et al., 2014; Wang et al., 2016). Researchers have shown that the injection of hUCB-MSCs throughout the early stage of ischemic brain injury decreased the IL-1β, IL-6, and TNF-α expression levels in the serum and increased IL-10 expression levels.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that, transplantation of human umbilical cord blood mesenchymal stem cells (hUCB-MSCs) decreases the number of activated microglia and inhibits the permeation of immune cells and cellular apoptosis in the brain after ischemic brain injury (Yang et al., 2013; Zhu et al., 2014; Wang et al., 2016). Researchers have shown that the injection of hUCB-MSCs throughout the early stage of ischemic brain injury decreased the IL-1β, IL-6, and TNF-α expression levels in the serum and increased IL-10 expression levels.…”
Section: Discussionmentioning
confidence: 99%
“…For the detection of histopathological damage, sections were stained fixed in 10% formaldehyde and embedded in paraffin. The sections (5–6 µ m) were then stained with H&E for pathomorphological analysis, as described previously ( 20 ).…”
Section: Methodsmentioning
confidence: 99%
“…Acupuncture of Sishencong [25] can nourish heart and tranquilize mind and soothe liver and relieve depression, thus improving the structure of sleep; acupuncture of Baihui [26] around which there are abundant blood vessels can treat insomnia. Modern studies have also confirmed that acupuncture can make patients in a state of qi-blood harmony, peaceful yin and compact yang in the treatment of insomnia [27,28] , thus improving the sleep quality of patients. Purpose of this paper is to collect high-quality clinical randomized controlled trials and strictly evaluate and analyze them one by one and then statistically process the data by quantitative synthesis and objectively evaluate them, so as to draw the comprehensive conclusion.…”
Section: Discussionmentioning
confidence: 99%